THE PRESIDENT'S ANXIETY WHEN HE DOES NOT HAVE MAJORITY SUPPORT IN PARLIAMENT - Johan Akbari; Amalia Syauket (Bhayangkara Law Review, 2024)
The president's decision immediately after being elected is how the state government to be run obtains the majority support in parliament (DPR RI). This confusion is natural considering that the presidential system must involve the people's representative institution as a form of democratic government and simultaneously implement the indirect democratic system. In the context of the power relationship between the president and the House of Representatives, sometimes it causes turmoil when the president/vice president is not supported by the majority of the House of Representatives, even to the point of worrying that impeachment may be carried out. The author uses a qualitative approach with a secondary database-document analysis with an instrumental case study of the 2009-2014 Presidential Administration to find out what are the reasons for the president's upset when he does not have the majority support in Parliament and what is the solution. The results of the study show that the reason for President SBY's upset is that he is worried that there will be a political impasse due to political tensions. The solution to overcome the chaos so that there is no political stalemate, with President SBY's accommodating-compromising attitude towards political parties in Parliament. This attitude is possible because of the pragmatic and transactional attitude as the ideological relationship of political parties which tend to be moderate and centripetal-to to national integration.